2018
DOI: 10.1186/s12886-018-0926-8
|View full text |Cite
|
Sign up to set email alerts
|

Embedding of lamellar hole-associated epiretinal proliferation combined with internal limiting membrane inversion for the treatment of lamellar macular hole: a case report

Abstract: BackgroundWe recently reported that lamellar macular hole (LMH) with lamellar hole-associated epiretinal proliferation (LHEP) can be effectively treated by embedding the LHEP into the retinal cleavage to improve foveal contour and visual acuity. Here, we report a case of LMH with LHEP for which we performed embedding of the LHEP combined with internal limiting membrane (ILM) inversion. We then evaluated the effects of this surgery on macular morphology and visual functions.Case presentationA 62-year-old man pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
(27 reference statements)
1
12
0
1
Order By: Relevance
“…Comparing these two surgical methods, the difference between them lies in the disposition of ERM and ILM. Instead of peeling the membrane, the new method double inverted the ERM and flapped the ILM [28,29]. This kind of surgery can preserve the LHEP and promote LHM recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing these two surgical methods, the difference between them lies in the disposition of ERM and ILM. Instead of peeling the membrane, the new method double inverted the ERM and flapped the ILM [28,29]. This kind of surgery can preserve the LHEP and promote LHM recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with the regular surgery method, the main difference is about the disposition of ERM and ILM. Instead of peeling the membrane, in the new method, ERM was double inverted and ILM was apped [28,29]. This kind of surgery can retain LHEP and promote the recovery of LHM, and a study indicated that the development of LHEP might be a recovery progress of LMH [15].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing these two surgical methods, the main difference exists in the disposition of ERM and ILM. Instead of peeling the membrane, in the new method, ERM is double inverted and ILM is apped [28,29]. This kind of surgery can retain LHEP and promote the recovery of LHM.…”
Section: Discussionmentioning
confidence: 99%